PHENOTYPE CHARACTERISTICS OF CROSSING PURPLE CORN AND SWEET YELLOW CORN (ZEA MAYS L.) IN GENERATION F4 - Maemunah, Maemunah; Samudin, Sakka; Mustakim, Mustakim; Akbar, Ali; Jeki, Jeki; Mas'ud, Hidayati (Universitas Tadulako, 2024)
Phenotypic characters in crossed plants is very important to find out the success of a cross and the differences in characters between one type and another. The purpose of this study was to identify and determine the best phenotypic characters resulting from crosses of maize plants in the F4 generation. This research was carried out on agricultural land in Oloboju Village (Bulu Pontu Jaya SP2), at an altitude of 176 meters above sea level, with a latitude of 1ᵒ00'21